2019
DOI: 10.4086/toc.2019.v015a012
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Locally decodable codes (LDCs) are error correcting codes that allow for decoding of a single message bit using a small number of queries to a corrupted encoding. Despite decades of study, the optimal trade-off between query complexity and codeword length is far from understood. In this work, we give a new characterization of LDCs using distributions over Boolean functions whose expectation is hard to approximate (in L ∞ norm) with a small number of samples. We coin the term "outlaw distributions" for such dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In contrast with other combinatorial objects such as expander graphs, the probabilistic method has so far not been successfully used to beat the best explicit LDC constructions. In [BDG19], a probabilistic framework was given that could in principle yield best-possible LDCs, albeit non-constructively. A special instance of this framework connects LDCs with a probabilistic version of Szemerédi's theorem alluded to above.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with other combinatorial objects such as expander graphs, the probabilistic method has so far not been successfully used to beat the best explicit LDC constructions. In [BDG19], a probabilistic framework was given that could in principle yield best-possible LDCs, albeit non-constructively. A special instance of this framework connects LDCs with a probabilistic version of Szemerédi's theorem alluded to above.…”
Section: Introductionmentioning
confidence: 99%
“…In [BDG19] it is shown that there exist of k-query LDCs of message length Ω(ρ k N) and codeword length O(N). As such, Szemerédi's theorem with random differences, in particular lower bounds on ρ k , can be used to show the existence of LDCs.…”
Section: Introductionmentioning
confidence: 99%